posted by Katie on .
Simplify each expression. Assume that no denominators are zero. Write each answer without using negative exponents.
The ^'s mean they're exponents
------------ <- division
numerator: y^-3y^-4y^0 = y^(-3-4)= y^-7
denominator: 2^3 * y^-6 = 8y^-6
numerator/denom= y^-7/8y^-6= 1/8 * y^(-7+6)
= 1/8 y^-1= 1/(8y)
I would multiply the denominator by itself three times, then move the terms with negative exponents up or down, changing the sign of the exponent, then combine terms. I hope this helps.